Navigating the postgraduate terrain through a community of practice: Reflections of novice academics - van Laren, Linda; Mudaly, Ronicka (South African Journal of Higher Education, 2016)
This article explores how academics make the transition from teaching mainly on undergraduate programmes to teaching a postgraduate module. It reflects on what enables learning to occur through participation in a community of practice, where the community comprises academics at different levels who teach the same postgraduate module. Through self-study methodology, where data was sourced from the reflective diaries of the authors, entry into and sustained participation in the postgraduate terrain are detailed. The findings reflect the types of support which facilitate professional development of academics. A view is provided into the private narratives of academics as they assume a “boundary identity trajectory” when they approach the nexus of undergraduate and postgraduate teaching.